Social Media Advertising for Achieving Long-term Marketing Objectives - Abashidze, Irakli (European Scientific Journal, ESJ, 2023)
Increasing competition in consumer markets forces businesses to elaborate marketing plans focused on long-term perspectives. This is important in today's fluctuating and unpredictable business environments, where a high level of competitiveness and a positive reputation is the premise of survival for a business. Otherwise, it will be unable to retain its share of consumer markets and make plans focused on long-term periods. In this regard, social media advertising is one of the most powerful strategies to reach various marketing goals: brand awareness and high brand value, positive reputation and word of mouth, growing customer base, high ROAS (return on ad spend) in short-term and CLV (customer lifetime value) in the long run. Therefore, it is necessary to research social media advertising to achieve long-term marketing goals. The paper deals with various issues, including social media advertising opportunities, ways of attracting and retaining customers, raising brand awareness, and elaborating strategies focused on long-term results. The discussion provided in the paper is a result of the literature review and the author's observations. Each part of the paper contains recommendatory remarks for achieving long-term marketing goals by using social media advertising strategies. A brief conclusion summarizes the paper.